2002
DOI: 10.1002/jcp.10060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and hypoxia on TGFβ1 receptor expression and signal transduction in human dermal fibroblasts: Impact on cell migration

Abstract: Wound healing is critically affected by age, ischemia, and growth factors such as TGFbeta1. The combined effect of these factors on fibroblast migration, an essential component of wound healing, is poorly understood. To address this deficiency, we examined expression of TGFbeta receptor type I and II (TGFbetaRI and RII) under normoxia or hypoxia (1% O(2)) in cultured human dermal fibroblasts (HDFs) from young (ages 24-33) and aged (ages 61-73) adults. TGFbetaRI and RII expression was similar in both groups und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 34 publications
5
50
1
1
Order By: Relevance
“…109,110 Mogford et al reported that fibroblasts grown in a chronically hypoxic environment expressed lower levels of type I and type II TGF-b 1 receptors (TGFbRI & II). 111 This supported previous work by others which demonstrated that primary dermal fibroblasts exposed to acute hypoxic conditions ( < 1 week) in vitro, results in cellular proliferation, TGF-b 1 expression and type I collagen production. However, exposure to prolonged culture in hypoxic conditions ( > 1 week), thus, mimicking an ischemic dermal environment, did not support these processes.…”
supporting
confidence: 91%
“…109,110 Mogford et al reported that fibroblasts grown in a chronically hypoxic environment expressed lower levels of type I and type II TGF-b 1 receptors (TGFbRI & II). 111 This supported previous work by others which demonstrated that primary dermal fibroblasts exposed to acute hypoxic conditions ( < 1 week) in vitro, results in cellular proliferation, TGF-b 1 expression and type I collagen production. However, exposure to prolonged culture in hypoxic conditions ( > 1 week), thus, mimicking an ischemic dermal environment, did not support these processes.…”
supporting
confidence: 91%
“…Human dermal fibroblasts (HDF) were obtained per protocol of the IRB and Office for the Protection of Research Subjects at Northwestern University and cultured as previously described (Mogford et al, 2002). Cells were seeded at a density of 5,000 cells per well in 96-well plates.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Ageing is a universal process affecting most cells, and concurrent studies in vitro have confirmed that the age-related delay in angiogenesis is associated with several deficits in cell functions. The latter include slowed migration of aged microvascular endothelial cells (Reed et al, 2000) and fibroblasts (Reed et al, 2001;Mogford et al, 2002); lower nitric oxide (NO) production and increased sensitivity of endothelial cells to apoptotic stimuli (Vasa et al, 2000;Hoffmann et al, 2001;Chavakis and Dimmeler, 2002); a defective response in aged cells to the mitogenic effects of vascular endothelium growth factor (VEGF) (Rivard et al 1999) and the antiproliferative effects of transforming growth factor (TGF)-β1 (McCaffrey and Falcone, 1993).…”
Section: Effect Of Ageing and Caloric Restriction Regimen On Rat Aortmentioning
confidence: 99%